2019
DOI: 10.3389/fmicb.2019.00462
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Techniques Complement Culture-Based Assessment of Bacteria Composition in Mixed Biofilms of Urinary Tract Catheter-Related Samples

Abstract: Urinary or ureteral catheter insertion remains one of the most common urological procedures, yet is considered a predisposing factor for urinary tract infection. Diverse bacterial consortia adhere to foreign body surfaces and create various difficult to treat biofilm structures. We analyzed 347 urinary catheter- and stent-related samples, treated with sonication, using both routine culture and broad-range 16S rDNA PCR followed by Denaturing Gradient Gel Electrophoresis and Sanger sequencing (PCR-DGGE-S). In 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…It has been shown that type 3 pili together with type 1 are strictly required to cause catheter-associated UTIs (CAUTIs), a common hospital-acquired infection [45]. Most CAUTIs are polymicrobial, usually involving K. pneumoniae in association with P. mirabilis or this latter in co-infection with E. coli, highlighting the adoption of shared strategies to colonize and reside within human hosts [46]. Hence, targeting adhesive structures represents an excellent option to prevent and treat UTIs.…”
Section: Treasure Of Chaperone-usher Adhesinsmentioning
confidence: 99%
“…It has been shown that type 3 pili together with type 1 are strictly required to cause catheter-associated UTIs (CAUTIs), a common hospital-acquired infection [45]. Most CAUTIs are polymicrobial, usually involving K. pneumoniae in association with P. mirabilis or this latter in co-infection with E. coli, highlighting the adoption of shared strategies to colonize and reside within human hosts [46]. Hence, targeting adhesive structures represents an excellent option to prevent and treat UTIs.…”
Section: Treasure Of Chaperone-usher Adhesinsmentioning
confidence: 99%
“…(UR1-UR3), and Enterobacter spp. (UR13-UR14) identifications are difficult to compare due to different levels of taxonomy assignment by the method [47], while there is a significant positive correlation amongst other results for both conventional and genomics methods. A possible explanation for this difficulty might be related to bacterial nomenclature, taxonomy and very high sequence identity.…”
Section: S Rrna Sequencing Resultsmentioning
confidence: 99%
“…Urinary and ureteral catheter insertion is one of the most common urological interventions. At the same time, an inserted catheter is a condition changing the urinary tract micro-environment [ 29 , 30 , 31 ], promoting bacterial [ 30 ] and fungal colonization [ 32 ], and is a crucial risk factor for urinary tract infection (UTI).…”
Section: Introductionmentioning
confidence: 99%
“…A. schaalii was one of the most prevalent bacteria in a large cohort of urinary tract catheter samples, in earlier published observational study [ 30 ]. Kotaskova et al [ 30 ], and others [ 10 , 16 , 19 , 33 ] were able to identify A. schaalii exclusively by broad-range molecular techniques.…”
Section: Introductionmentioning
confidence: 99%